Color Stability of Coated Stainless Steel Arch wires Measured by Visible Spectrophotometer (An In-Vitro Study) - Abeer Basim Mahmood (Journal of Global Pharma Technology, 2018)
Background: Aesthetic archwires are used to overcome the aesthetic problems of stainless steel wires but the color of the coating layer can be changed with time when exposed to oral environments. The aim of this study was to evaluate the degree of color change of different aesthetic archwires from different companies and under different coloring solutions. Materials and Methods: 150 samples of coated archwires from 3 companies (Highland, G&H and Dany) were immersed 5 solutions (artificial saliva, turmeric, tea, coffee and Miranda) to evaluate the degree of color changes after 7, 14 and 21 days using visible spectrophotometer. Data were collected and analyzed using ANOVA and post hoc Turkey’s tests. Results: Turmeric solution caused high color change in contrast to Miranda solution. Aesthetic archwires from Highland company showed the highest degree of color change than archwires from other companies. Conclusions: Turmeric solution produced more discoloration than other solutions and the effects of these solutions are related to different chemical compositions of those solutions.Keywords: Aesthetic arch wires, Staining drinks, Turmeric, Tea, Coffee, Miranda.